PERANCANGAN STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) DALAM MENDORONG KONVERSI PENGGUNAAN PRODUK BY.U BY TELKOMSEL SEBAGAI COPYWRITER - Nadya Syafiqa; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
by.U is a digital mobile service launched by Telkomsel, primarily targeting Generation Z andyoung, digitally active users. However, by.U usage among high school and vocational schoolstudents in Semarang remains relatively low. A survey of 814 students from four schoolsaffiliated with Telkomsel's educational platform, Skul.id, found that only 46 students, orapproximately 5.7%, were active by.U SIM card users. Furthermore, the survey also showedthat the perceived risk of the service remains quite high, at 52.2%, while purchase intentionremains at 20.8%. To address these issues, an integrated marketing communications campaignwas designed through the